(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Although the rule of law is globally and regionally increasingly in focus, there are various attempts to blur the separation of powers and weaken judiciary, its integrity and independence through institutional reforms and in individual cases. Judicial independence and integrity are under threat in several EU member states, including Hungary, Romania, and Poland. Judicial crises in the EU jeopardize essential principle of mutual recognition in judicial matters and free movement of goods, services, people and capital. The recent decision of the Irish high judge to refuse to extradite a suspected drugs trafficker to Poland due to concerns about the integrity of the Polish justice system, re-confirms the relevance of the rule of law for the EU and judgement of Court of Justice of EU (CJEU) in case LM, C216/18 PPU. Following Court of Justice decisions related to the Polish judiciary are relevant for shaping Court of Justice position on independence and impartiality of judiciary (i.e. judgment of 24 June 2019, Commission v Poland, C619/18; judgement of 19 November 2019, joined cases A.K. and Others v Krajowa Rada Sadownictwa, C585/18, C624/18 and C625/18). Backsliding on rule of law in the EU is a possibility that the Court of Justice of the European Union is seeking to prevent and mitigate. In doing so, the Court of Justice is establishing EU standards on independence and accountability of judiciary. There have also been signs that citizens care about the rule of law, highlighting he importance of demand-side initiatives that foster citizen voice. In all, in the current European environment, the rule of law is highly visible and increasingly relevant for citizens, businesses, governments, and EU institutions, especially EU Court of Justice. In the article author is reviewing Court of Justice decisions relevant for the independence of judiciary, its influence on national legislators, European Commission policy towards access countries and strengthening requests for genuine reform of justice in candidate countries. Consequently, author emphasized the advantages of active role of Court of Justice in establishment of EU standards on independence and impartiality of judiciary in order to prevent further erosion of rule of law, separation of powers and position of judiciary in the member states.